Characterization of a Selenium-Tolerant Rhizosphere Strain from a Novel Se-Hyperaccumulating Plant Cardamine hupingshanesis - Xinzhao Tong; Linxi Yuan; Lei Luo; Xuebin Yin (The Scientific World Journal)
A novel selenium- (Se-) hyperaccumulating plant, Cardamine hupingshanesis, accumulating Se as a form of SeCys2, was discovered in Enshi, Hubei, China, which could not be explained by present selenocysteine methyltransferase (SMT) theory. However, it is interesting to investigate if rhizosphere bacteria play some roles during SeCys2 accumulation. Here, one Se-tolerant rhizosphere strain, Microbacterium oxydans, was isolated from C. hupingshanesis. Phylogenetic analysis and 16S rRNA gene sequences determined the strain as a kind of Gram positive bacillus and belonged to the family Brevibacterium frigoritolerans. Furthermore, Se tolerance test indicated the strain could grow in extreme high Se level of 15.0 mg Se L−1. When exposed to 1.5 mg Se L−1, SeCys2 was the predominant Se species in the bacteria, consistent with the Se species in C. hupingshanesis. This coincidence might reveal that this strain played some positive effect in SeCys2 accumulation of C. hupingshanesis. Moreover, when exposed to 1.5 mg Se L−1 or 15.0 mg Se L−1, As absorption diminished in the logarithmic phase. In contrast, As absorption increased when exposed to 7.5 mg Se L−1, indicating As metabolism processes could be affected by Se on this strain. The present study provided a sight on the role of rhizosphere bacteria during Se accumulation for Se-hyperaccumulating plant.